Effect of different cooking methods on nutritional intake and different storage treatments on nutritional losses of abalone. (30th May 2022) - Li, Quanquan; Lu, Jie; Chang, Yajie; Shen, Guiping; Feng, Jianghua
Highlights: Composition and nutritional profiles of abalones were obtained by 1 H NMR spectroscopy. Boiling was recommended as the best cooking method of abalone. The optimum storage condition of abalone could be within one day under 4 °C. The suitable storage conditions were recommended to avoid the losses of the nutrients. Abstract: As the most important marine edible shellfish, the nutritional quality of abalone has been paid attention. In this study, the chemical and nutritional compositions of abalones were obtained, and three cooking methods, steaming, boiling and frying, were evaluated by in vitro gastric digestion simulation to understand their nutritional changes by 1 H NMR spectroscopy combined with multivariate statistical analyses. The nutritional losses were also monitored under different cold storage conditions. The results indicated that boiling can keep more amino acids and fatty acids than steaming and frying, thus being recommended as the best cooking method of abalone. The abalone could maintain fresh within one day under 4 °C, and the deterioration process occurred subsequently. These results help to understand the digestion of cooked abalone and the changes of nutrients through storage and cooking process, leading to a scientific recommendation of cooking method and storage condition for healthy eating.